Anterior segment optical coherence tomography angiography for iris vasculature in pigmented eyes. Issue 7 (18th August 2020) - Ang, Marcus; Devarajan, Kavya; Tan, Anna CS; Ke, Mengyuan; Tan, Bingyao; Teo, Kaiying; Sng, Chelvin C.A.; Ting, Daniel S; Schmetterer, Leopold
Abstract : Purpose: To compare anterior segment optical coherence tomography angiography (AS-OCTA) systems in delineating normal iris vessels and iris neovascularisation (NVI) in eyes with pigmented irides. Methods: Prospective study from January 2019 to June 2019 of 10 consecutive patients with normal pigmented iris, had AS-OCTA scans with a described illumination technique, before using the same protocol in five eyes with NVI (clinical stages 1–3). All scans were sequentially performed using a spectral-domain OCTA (SD-OCTA), and a swept-source OCTA (SS-OCTA, Plex Elite 9000). Images were graded by two masked observers for visibility, artefacts and NVI characteristics. The main outcome measure was iris vessel density measurements comparing SS-OCTA and SD-OCTA systems. Results: The median age of subjects was 28 (20–35) years, and 50% were female. The paired mean difference of iris vessel density measurements was 11.7 (95% CI 14.7 to 8.1; p=0.002), SS-OCTA detecting more vessels than SD-OCTA. The inter-rater reliability for artefact score (κ=0.799, p<0.001) and visibility score (κ=0.722; p<0.001) were substantial. Both AS-OCTA systems were able to detect NVI vessels with a fair agreement (κ=0.588), with clearer NVI characteristics in stage 1/2 compared to stage 3 NVI (mean difference NVI score: 2.7±0.4, p=0.009). Conclusion: The SS-OCTA was better able to delineate iris vessels in normal pigmented irides compared to SD-OCTA. Both AS-OCTA systems identified NVI characteristics based on its atypical configuration or location, but further improvements are needed to allow for more accurate objective, serial quantification for clinical use.